EFEKTIFITAS PEMANFAATAN TELEHEALTH NURSING TERHADAP PENINGKATAN SELF-MANAGEMENT DI MASA PANDEMI COVID -19 PADA PASIEN DIABETES MELLITUS POSYANDU SEHAT MANUNGGAL KARTASURA - Listrikawati, Martini; Batubara, Intan Maharani; Muhlishoh, Arwin; Kusumawati, Heni Nur; Fitriyani, Noor (Journal of Advanced Nursing and Health Sciences, 2023)
Indonesia is currently facing a triple burden of disease which adds to the problems in society. The problems that arise are not only about the outbreak of new infectious diseases, the outbreak of old infectious diseases and the increase in non-communicable diseases from time to time, but also problems arising from the interaction between the three. The prevalence of Diabetes Mellitus is increasing from year to year and has an impact on the patient's self-management. This study aims to determine the effectiveness of using telehealth nursing to improve Self Management during the COVID-19 pandemic in Diabetes Mellitus patients at Posyandu Sehat Manunggal Kartasura. This research method is a quasi-experimental one group pre test post test. The research instrument used is the DSMQ questionnaire sheet which is used to measure the self-management of diabetes mellitus patients at Kartasura Health Charity Clinic and the provision of telehealth nursing interventions. The data analysis method used in this study was univariate analysis related to patient characteristics data and bivariate analysis using Independent Sample t-test data analysis with p<0.05, which means that there is an effectiveness in using telehealth.